In-office Eustachian tube balloon dilation under local anesthesia as a response to operating room restrictions associated with the COVID-19 pandemic - Sheppard, Sean C.; Beckmann, Sven; Caversaccio, Marco; Anschuetz, Lukas (Frontiers in Surgery, 2023)
Objective To evaluate the feasibility of local anesthesia for Eustachian tube balloon dilation as an in-office procedure for the treatment of Eustachian tube dilatory dysfunction as a response to the restriction measures of the coronavirus disease 2019 pandemic. Method Patients with Eustachian tube dilatory dysfunction refractory to nasal steroids undergoing Eustachian tube balloon dilation in local anesthesia were enrolled in a prospective observational cohort between May 2020 and April 2022. The patients were assessed by using the Eustachian tube dysfunction questionnaire (ETDQ-7) score and Eustachian tube mucosal inflammation scale. They underwent clinical examination, tympanometry, and pure tone audiometry. Eustachian tube balloon dilation was performed in-office under local anesthesia. The perioperative experience of the patients was recorded using a 1–10 visual analog scale (VAS). Results Thirty patients (47 Eustachian tubes) underwent the operation successfully. One attempted dilation was aborded because the patient displayed anxiety. Local anesthesia was performed by using topical lidocaine and nasal packing for all patients. Three patients required an infiltration of the nasal septum and/or tubal nasopharyngeal orifice. The mean time of the operation was 5.7 min per Eustachian tube dilation. The mean level of discomfort during the intervention was 4.7 (on a 1–10 VAS scale). All patients returned home immediately after the intervention. The only reported complication was a self-limiting subcutaneous emphysema. Conclusion Eustachian tube balloon dilation can be performed under local anesthesia and is well tolerated by most patients. In the patients reported in this study, no major complications occurred. In order to free operation room capacities, the intervention can be performed in an in-office setting with satisfactory patient feedback.